2022
DOI: 10.3389/fneur.2022.755316
|View full text |Cite
|
Sign up to set email alerts
|

Early Supported Discharge and Transitional Care Management After Stroke: A Systematic Review and Meta-Analysis

Abstract: ObjectiveTo investigate the available evidence on early supported discharge (ESD) and transitional care (TC) delivery service in patients with cerebrovascular disease.MethodsA systematic literature search was conducted to collect all available evidence on the use of ESD and TC services. We included cluster-randomized pragmatic trials or randomized controlled trials (RCTs) that recruited patients with stroke or transient ischemic attack to receive either conventional care or any care service intervention that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…This aligns with findings from the Riksstroke registry in Sweden which showed that those with first ever stroke who received ESD (n = 1495) were more satisfied with rehabilitation after discharge, reported less depression and better function compared to controls (n = 28,737) [ 55 ]. Our findings on important improvements reported by people after stroke following ESD such as improved mobility and the ability to resume valued activities also mirrors findings from systematic reviews of the effectiveness of ESD after stroke which have found improvements in participants’ activities of daily living [ADL] scores [ 18 ] and extended activities of daily living scores [ 17 ] in favour of ESD when compared to usual care.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This aligns with findings from the Riksstroke registry in Sweden which showed that those with first ever stroke who received ESD (n = 1495) were more satisfied with rehabilitation after discharge, reported less depression and better function compared to controls (n = 28,737) [ 55 ]. Our findings on important improvements reported by people after stroke following ESD such as improved mobility and the ability to resume valued activities also mirrors findings from systematic reviews of the effectiveness of ESD after stroke which have found improvements in participants’ activities of daily living [ADL] scores [ 18 ] and extended activities of daily living scores [ 17 ] in favour of ESD when compared to usual care.…”
Section: Discussionsupporting
confidence: 85%
“…A Cochrane review of ESD for people after stroke demonstrated a reduction in the length of hospital stay by 6 days [CI -3 to -8 days] and a reduction in long term dependency and admission to long term care [17]. A more recent review also demonstrated improved activities of daily living (ADL) scores for those receiving ESD compared to those receiving usual care [18]. ESD has also been proven to be cost effective [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the case of ADL outcomes, neutral findings or small effect sizes can be attributed to a ceiling effect. As underlined by similar studies, most participants started the experiment with an already high level of ADL functioning (Jee et al, 2022;Langhorne & Baylan, 2017). In some studies, transitional care programmes did not sufficiently target patients with stroke-related deficits or potential complications (Sit et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have added to the body of knowledge on the potential benefits of transitional care programmes in improving the motor performance, walking speed, and ADL performance of patients with stroke; however, their findings are inconclusive. Moreover, previous systematic reviews and meta‐analyses have also highlighted transitional care techniques that emphasize continuous rehabilitation through multidisciplinary teams and therapy‐based home rehabilitation, with patients receiving diverse stroke recovery care (Jee et al, 2022; Lin et al, 2020). However, it is unclear how the services should be planned and coordinated, as well as the intensity and duration of rehabilitation based on the outcome needs and preferences of patients and caregivers (Joo & Liu, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation